2007
DOI: 10.1161/circulationaha.106.653782
|View full text |Cite
|
Sign up to set email alerts
|

Transient Limb Ischemia Induces Remote Preconditioning and Remote Postconditioning in Humans by a K ATP Channel–Dependent Mechanism

Abstract: Background— Transient limb ischemia administered before a prolonged ischemic insult has systemic protective effects against ischemia-reperfusion (IR) injury (remote ischemic preconditioning [RIPC]). It has been demonstrated that protection from IR can be achieved by brief periods of ischemia applied at a remote site during an injurious ischemic event (remote postconditioning [RPostC]). Using an in vivo model of endothelial IR injury, we sought to determine whether RPostC occurred in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(115 citation statements)
references
References 53 publications
(52 reference statements)
4
106
1
2
Order By: Relevance
“…In addition, Ren et al [22] found that the protective effect of the limb remote IPC depended on numbers and duration of the limb ischemic stimulus. In the study of Loukogeorgakis et al [23], moreover, the strength of the protective effect afforded by the limb remote IPOC is related to the tissue volume exposed to the ischemic stimulus. A possible mechanism for this effect is that the inferior stimulus does not make the trigger tissue release enough humoral factors to completely activate the signal transduction pathways eliciting cardioprotection.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, Ren et al [22] found that the protective effect of the limb remote IPC depended on numbers and duration of the limb ischemic stimulus. In the study of Loukogeorgakis et al [23], moreover, the strength of the protective effect afforded by the limb remote IPOC is related to the tissue volume exposed to the ischemic stimulus. A possible mechanism for this effect is that the inferior stimulus does not make the trigger tissue release enough humoral factors to completely activate the signal transduction pathways eliciting cardioprotection.…”
Section: Discussionmentioning
confidence: 97%
“…They found that remote Postcon applied in an arm or leg at the onset of reperfusion significantly preserves flow-mediated vasodilatation. Protection was blocked by a non-selective K ATP channel blocker, glibenclamide [103]. A recent clinical observation reported by Bøtker et al at the American College of Cardiology 58th Annual Scientific Session in 2009 demonstrated that upper-limb ischemia with four 5/5 min inflation/deflation using a standard blood pressure cuff initiated during ambulance transfer (named as remote perconditioning) reduces myocardial infarct size measured by SPECT imaging after 30 days of standard PCI in STEMI patients.…”
Section: Remote Postconmentioning
confidence: 99%
“…In stroke and myocardial infarct patients, prompt application of remote IPC could limit the extent of infarct damage, especially considering the recent findings of ''post-conditioning'' [57].…”
Section: Potential Of Preconditioningmentioning
confidence: 99%